Model Kepemimpinan yang Ideal Dalam Penataan Organisasi Gereja - Simon Simon; Alvonce Poluan (SHAMAYIM: Jurnal Teologi dan Pendidikan Kristiani, 2021)
AbstractThe basic idea of this article comes from factual events there are disputes between the leaders of the church organization and the members they lead. Disputes are caused by the leadership model run by the leader in organizing the organization that does not match the expectations (expectations) of the subordinates. The research method used in the writing of this article is a qualitative method with a literature approach and in-person interviews. The description of this paper, the church organization stands on the permission of God initiated by His servants. With the organization, the church provides a sketch of who is the leader and who is being led. The leadership model needed in the organization of the church by a leader is non-tribalism, open to input and criticism, not concerned with personal interests but not to self-indulgence in practical politics. The achievement of organization missions is on the shoulders of the leader, whether to mobilize all the resources possessed by the organization components of the church. AbstrakIde dasar dari artikel ini berangkat dari peristiwa faktual, adanya perselisihan antara pemimpin  organisasi gereja dengan anggota yang dipimpin. Perselisihan itu timbul ditenggarai oleh model kepemimpinan yang dijalankan oleh si pemimpin dalam penataan organisasi tidak sesuai dengan ekspektasi (harapan) oleh bawahan. Metode yang peniliti gunakan dalam penulisan artikel ini adalah metode kualitatif dengan pendekatan kepustakaan disertai wawancara secara langsung. Uraian dari tulisan ini, organisasi gereja berdiri atas seijin Tuhan yang diprakarsai oleh hamba-hamba-Nya. Dengan adanya organisasi gereja memberikan sketsa siapa yang menjadi pemimpin dan siapa yang dipimpin. Model kepemimpinan yang dibutuhkan dalam penataan organisasi gereja oleh seorang pemimpin adalah tidak sukuisme, terbuka kepada masukan dan kritikan, tidak mementingkan kepentingan pribadi maupun golongan serta tidak menceburkan diri pada politik praktis. Tercapainya sebuah visi-misi organisasi ada dalam pundak sang pemimpin, apakah ia bisa menggerakkan semua sumber daya yang dimiliki oleh kompomen organisasi gereja tersebut.